Dynamic Governance Capabilities in Regional Budget Policy Formulation to Create Agile Bureaucracy During Covid-19 - Rozidateno Putri Hanida; Bimbi Irawan; Fachrur Rozi (Jurnal Manajemen Pelayanan Publik, 2021)
This pandemic period is the most difficult period for local governments, especially the pandemic has been going on for almost one fiscal year. The sudden arrival of the pandemic has forced the government to do budget refocusing. This study specifically wants to describe the dynamic governance capabilities of local governments in formulating regional budget policies during the pandemic or after the Covid-19 outbreak ends, so that in the future fiscal year, agile bureaucracy will be built in the regions. Another objective of this study is to describe the fundamental problems that occur in the budget formulation process and offer guidance related to how to solve problems in the budget preparation cycle for the 2021 fiscal year. The focus of the study is on the process of making budgeting policies in the regions, not on fiscal policies. This study uses a qualitative descriptive method, with data sources entirely obtained through secondary sources, so that this study can be called a literature research. The results of this study found that within the framework of thinking a head, local governments must be able to applicate using existing budgetary flexibility and exceptional spending procedures to fund first, so that the programs and activities to be carried out can be more flexible. Another thing that was found was the accelerating revision of regional finance regulation to secure a budget for the response through. During this pandemic, local governments continue to carry out planned programs and activities, so that regional budget absorption can be achieved and the economic life of the community can continue to develop.